A comparative study of clinical profile & investigative parameters of systemic lupus erythematosus patients with & without metabolic syndrome - Rajadhyaksha A.G.; Nitin Sarate; Shreepriya Mangalgi (International Journal of Medical Research and Review, 2018)
Introduction: The Metabolic Syndrome (MetS) often contributes to increased cardiovascular risk in patients with systemic lupus erythematosus (SLE) especially in younger age group. Determining the contribution of SLE phenotype and therapeutic exposures to the development of MetS in SLE patients would yield important insights into pathophysiology of cardiovascular events and help in Coronary Heart Disease (CHD) risk stratification.Objective: We aimed to get prevalence of metabolic syndrome in SLE patients & to correlate its presence with demographic, socioeconomic, clinical manifestations, serological parameters, pharmacological treatment, disease activity, disease duration & damage index.Method: A total 104 patients of SLE diagnosed as per American College of Rheumatology (ACR) criteria were enrolled during the study. Metabolic Syndrome was defined according to the American Heart Association & National Heart, Lung & Blood Institute modified National Cholesterol Education Programme Adult Treatment Panel III criteria (AHA/NHLBI modified NCEP/ATP III).Result: Out of 104 enrolled patients, MetS was present in 35 patients (33.7%). Higher mean age (32.8 vs 27 years), Higher Body Mass Index (26.65 vs 21.07kg/m2), Increased triceps skin fold thickness (20.46 vs 15.80 mm), longer disease duration (223.9wk vs 64.78 wk), the presence of lupus nephritis, hypertriglyceridemia, positive anti-ds DNA, higher serum creatinine, higher damage index & higher cumulative dose of steroids were associated MetS in SLE patients.Conclusion: Screening for metabolic syndrome in patients with SLE will be helpful to minimize morbidity and mortality.